Respuesta :
Answer:
Step-by-step explanation:
9 - 4x > = 5 or 4(-1 + x) - 6 > = 2
-4x > = 5 - 9 -4 + 4x - 6 > = 2
-4x > = -4 4x - 10 > = 2
x < = -4/-4 4x > = 2 + 10
x < = 1 4x > = 12
x > = 12/4
x > = 3
answer is : B
The compound inequality for 9 – 4x ≥ 5 or 4(–1 + x) – 6 ≥ 2 is:
Option A is correct.
A compound inequality is one that is formed by combining two simple inequalities. They are derived form of fundamental inequalities.
From the question:
- 9 – 4x ≥ 5 or 4(–1 + x) – 6 ≥ 2
The first thing to do is to open the brackets and move the like terms to the same sides.
So,
9 - 5 ≥ 4x or -4 + 4x - 6 ≥ 2
4 ≥ 4x or -10 + 4x ≥ 2
4 ≥ 4x or 4x ≥ 10 + 2
4 ≥ 4x or 4x ≥ 12
4x ≥ 4 or 4x ≥ 12
Divide both sides by 4
[tex]\mathbf{\dfrac{4x}{4} \geq \dfrac{4}{4}} \ \ or \ \ \mathbf{\dfrac{4x}{4} \geq \dfrac{12}{4}}[/tex]
x ≥ 1 or x ≥ 3
Therefore, the compound inequality of 9 – 4x ≥ 5 or 4(–1 + x) – 6 ≥ 2 is:
x ≥ 1 or x ≥ 3
Learn more about compound inequality here:
https://brainly.com/question/24540195?referrer=searchResults